JUSTICE AND RATIONAL DELIBERATION IN AL-FARABI’S PHILOSOPHY - Abdullah Moussa; Noura Abed (International Journal of Innovative Technologies in Social Science, 2025)
Al-Farabi's philosophy presents a comprehensive view of human nature and the role of the state in facilitating the pursuit of happiness and perfection. He views human beings as inherently social creatures who cannot live in isolation and are dependent on the state for support, security, and adherence to laws. In his view, the state exists not only to provide for the needs of its citizens but also to ensure that individuals can pursue virtuous qualities and attain happiness.The concept of justice, as articulated by Al-Farabi, is central to the state's function. Justice is intertwined with other essential values, such as right, freedom, and equality. This leads to a deeper exploration of justice’s moral dimensions—its importance in society, its connection to human rights, and its relationship to ethics.Al-Farabi's philosophy raises several important questions:What is the moral dimension of justice as a value? Is justice an absolute or relative value? Does prudence direct justice towards the common good and avoid evil?Thus, Al-Farabi's thought positions justice as a fundamental moral value that should be upheld by individuals and the state alike. Through the application of prudence and guided by the principles of virtue, justice helps form a society that supports the flourishing of its members and contributes to the greater good.